Plasticizing effect on polyethylene oxide doped ammonium perchlorate. (August 2022) - Pratap, Rana; K Singh, Pramod; Sharma, Tejas; Singh, Vijay; Alheety, Mustafa A; Kumar, Sushant; Madkhli, Aysh Y; Noor, IM; Zakariya'u, Ibrahim; Singh, Abhimanyu
Plasticized polymer complex films of polyethylene oxide with ammonium perchlorate (NH4 ClO4 ) are synthesized by using solution cast technique. Propylene carbonate (PC) used as dopant to enhance conductivity of polymer electrolyte. The prepared films are characterized in detail using X-ray diffraction, infrared spectral analysis, transient ionic current, and electrochemical impedance studies. Plasticized polymer electrolyte shows high ionic conductivity (∼10 −4 S/cm) which appear as novel electrolyte for electrochemical devices.